Museums, exchanges, and their contribution to Joseph Nye’s concept of ‘soft power’ - Hoogwaerts, Leanne (Museum and Society, 2017)
This paper discusses the role that museums and art institutions have in recent years played in international relations, and their contribution to the concept of soft power, coined by Joseph Nye; referring to a country’s ability to persuade rather than coerce through elements of ‘hard’ power such as the threat of a strong military (Nye 2004). Using as examples the exchanges of the Cyrus Cylinder between Iran and the British Museum, and the loan of Picasso’s Buste de Femme (1943) from the Dutch Van Abbemuseum to the International Academy of Art Palestine, the paper argues that through their role as ‘national expressions of identity’ and ‘memory institutions’, museums and art institutions are able to make a positive contribution to international relations by engendering mutual respect and understanding in ways that other forms of dialogue may be unable to. As soft power is an area that still requires significant research, this paper aims to contribute observations and case studies that may affirm its influence. Key Words: cultural diplomacy, museums, soft power, international relations, cultural exchange